Mutagenesis of Protoplasts and Regeneration of Mycelium in the Mushroom Volvariella volvacea - Mukherjee, M. (1986)
Regenerating protoplasts were obtained from mycelial culture of the mushroom Volvariella volvacea by the action of the lytic enzyme Novozym 234 in the presence of 0.01 M phosphate buffer (pH 6.0) containing 0.6 M NaCl. Regeneration was found to be poor in liquid medium, but more than 50% regeneration was achieved on solid 2% agar medium overlaid with 0.5% agar. Protoplasts of V. volvacea were found to be highly sensitive to the killing action of both UV irradiation and N-methyl-N′-nitro-N-nitrosoguanidine. However, no morphological or auxotrophic mutants could be obtained from protoplasts by chemical mutagenesis. Four types of morphological mutants and one auxotrophic (adenine-negative) mutant were obtained from UV-irradiated protoplasts. The adenine-negative mutant of V. volvacea was found to be stable, not losing auxotrophy on repeated subculture.